2018
DOI: 10.1038/s41385-018-0044-1
|View full text |Cite
|
Sign up to set email alerts
|

MAdCAM costimulation through Integrin-α4β7 promotes HIV replication

Abstract: Human gut associated lymphoid tissues (GALT) play a key role in the acute phase of HIV infection. The propensity of HIV to replicate in these tissues however, is not fully understood. Access and migration of naïve and memory CD4+ T cells to these sites is mediated by interactions between integrin α4β7, expressed on CD4+ T cells, and MAdCAM, expressed on high endothelial venules. We report here that MAdCAM delivers a potent costimulatory signal to naïve and memory CD4+ T cells following ligation with α4β7. Such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 59 publications
2
41
0
Order By: Relevance
“…In addition, α 4 β 7 can deliver costimulatory signals to CD4 + T cells that impact cell activation, proliferation and apoptosis [ 81 , 82 ]. We recently reported that MAdCAM -mediated costimulation supports HIV replication in α 4 β 7 high CD4 + T cells [ 19 ]. Whether V2 signaling through α 4 β 7 can similarly facilitate HIV replication requires additional investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, α 4 β 7 can deliver costimulatory signals to CD4 + T cells that impact cell activation, proliferation and apoptosis [ 81 , 82 ]. We recently reported that MAdCAM -mediated costimulation supports HIV replication in α 4 β 7 high CD4 + T cells [ 19 ]. Whether V2 signaling through α 4 β 7 can similarly facilitate HIV replication requires additional investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that α 4 β 7 functions simply as an attachment factor [ 18 ]. However, gp120 binding to α 4 β 7 , like mucosal addressin cellular adhesion molecule (MAdCAM) transduces signals to primary CD4 + T cells, suggesting that such signals may be relevant to infection in vivo [ 9 , 17 , 19 ]. In this regard we have recently reported that MAdCAM delivers a signal to CD4 + T cells that promotes cellular activation and viral replication [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rh-α 4 β 7 does not block viral entry into CD4 + T cells and has weak anti-HIV-1 activity in vitro [8, 18, 19]. We have recently shown that signaling through α 4 β 7 can promote HIV-1 replication [20] and, in this regard, we previously demonstrated that Rh-α 4 β 7 blocks α 4 β 7 from adopting an active conformation that is critical for this signaling [21].…”
Section: Introductionmentioning
confidence: 99%
“…13 Of note, MAdCAM-mediated T-cell costimulation through 4 7 was shown to enhance HIV-1 replication in vitro. 20 Interestingly, the Envs of some transmitter/founder (T/F) HIV-1 strains were reported to bind efficiently to 4 7 21 and there was an association between a motif in the gp120 leader sequence and viral transmission, 22 suggesting that posttranslational modifications of gp120, such as the level and quality of glycosylation, may influence 4 7 interaction. However, some authors have questioned the frequency of interaction with 4 7 among different HIV-1 isolates, including T/F isolates.…”
Section: Is a Non-essential Receptor For Hiv-1 Gp120mentioning
confidence: 99%